Farmer-Herder Conflicts: A Case Study of Fulani Herdsmen and Farmers in The Agogo Traditional Area Of The Ashanti Region - Baidoo, I. (University of Ghana, 2014)
This thesis examines conflicts over natural resources between pastoralists and indigenous farming communities in Agogo, in the Ashanti Region of Ghana. In recent years, Agogo has gained much coverage in the media over these conflicts. This study attempts to unravel the underlying causes of these conflicts. It argues that the conflicts are shaped by three different interests: farmers, herders and chiefs. The chiefs are interested in gaining revenues from land and natural resources by releasing them to migrants, including herders. This creates pressures on local resources and affects farmers‘ management of fallow land. It results in herders encroaching into farming areas and farmers moving into herding areas. The pressure on resources and encroachment of cattle onto farm lands, where they destroy crops, results in increasing tensions between herders and farmers which breaks out into violent confrontations. The study investigates the conditions and arrangements under which lands are released to migrants or herders. It examines specific instances of conflicts, and the moral discourses around migrants and pastoralists. The study employed qualitative methods of research by conducting in-depth and unstructured interviews to solicit information from farmers, pastoralists, chiefs, assembly members and a veterinary officer. The study also made use of policy documents, committee reports and police records. The interview sought to examine the nature of livelihood activities, relations with other groups, types of conflicts, perceptions of conflicts and cultural and moral perceptions of other groups. Media reports tend to exaggerate violent conflicts and engage in ethnic stereotyping while ignoring the structural relations that produce the conflict, which lie in the ability of chiefs to sell and commercialise resources to outsiders without consulting with local communities.